EVALUASI DAMPAK PENYULUHAN PERTANIAN DI KECEMATAN IMOGIRI KABUPATEN BANTUL - Yulianto, Gunawan (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2009)
This research aimed to evaluate the impact of Agriculture Extension activities by THL TBPP (contract-based extension workers) in the sub-district of Imogiri, Bantul. This research combined quantitative descriptive and qualitative methods. To obtain a profound comprehension on the observed items, data collecting was done by questionnaire, observation and Focus Group Discussions. Instrument validity consisting of validity and factor analysis resulted in r count of a = 5%; > 0.444 in which 18 items are confirmed as valid. The instrument reliability with the alpha cofficient formula all together was equal to 0.918. Quantitative data was processed using the SPSS 17.0 for 14 Wendows. The research recognized improvements in the following points: l) field agriculture extension activities after the THL TBPP program (66.7%o); 2) farmers behavior changes and farm activities (56.7%